Statins in Chronic Kidney Disease: Cardiovascular Risk and Kidney Function. Issue 1 (January 2014) - Deedwania, Prakash C.
Abstract : : Chronic kidney disease (CKD) represents a serious public health concern. It has been associated with a significant burden of cardiovascular disease and studies have linked decreases in estimated glomerular filtration rate to higher incidences of cardiovascular events and mortality. Evidence from randomized clinical trials have shown that statins are a safe and effective treatment for improving cardiovascular outcomes in primary and secondary cardiovascular disease prevention in patients with CKD; despite this, statins are often underutilized in these patients. In addition to cardiovascular benefits, statin therapy may be associated with improvements in renal function in patients with kidney disease. Some statin treatment regimens have been shown to slow decline in kidney function, and some trials have found that intensive statin therapy improved kidney function. This review examines improved cardiovascular outcomes with statin treatment in patients with CKD (excluding end–stage renal disease) and investigates the effects of statin therapy on kidney function.